Lead (Pb) accumulation in the Indonesian intensive farming system - Rahman, Arif (Journal of Smart Agriculture and Environmental Technology, 2023)
One of the factors of soil pollution in paddy soil is the heavy metal lead (Pb). Lead is an element that is not essential for plants, with a content ranging from 0.1 - 10 µg/kg, and in various plants, it normally ranges from 0.5 - 3.00 µg/kg. This study aims to determine the content of lead (Pb) in soil and rice plants, as well as some of the chemical properties of the soil in the central rice area located in Marga Cinta, Belitang Madang Raya District, East Ogan Komering Ulu, South Sumatra, Indonesia. This study used a detailed survey method with a working map scale of 1:9,000. The paddy field studied covered 96 hectares divided into 6 locations, which were sampled using a random sampling method. Each location had 5 soil drilling points, and composite samples were created. Soil sampling was carried out by augering at a depth of 0-30 cm. The results showed that the content of lead (Pb) in paddy soil ranged from 9.90 – 12.18 µg/g with an average of 10.56 µg/g, while the content of lead (Pb) in rice plants was below the detection limit of the tool, with a value of <0.0002 µg/g. The conclusion from the study was that the content of the heavy metal lead (Pb) in paddy soil and rice plants at the study site was still below the threshold.